2019
DOI: 10.1186/s40677-019-0135-7
|View full text |Cite
|
Sign up to set email alerts
|

The relationship among the premonitory factors of landslide dam failure caused by seepage: an experimental study

Abstract: Background: A landslide dam always has the potential for catastrophic failure with high risk for life, cost and, property damage at the downstream site. The formation of a landslide dam is a natural process; thus, minimizing the risk due to its failure is important. Landslide dam failure can be categorized into three types: seepage failure, overtopping and slope failure. As described by other researchers, the established premonitory factors of landslide dam failure are hydraulic gradients, seepage and turbidit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 20 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…This phenomenon can also be found in the prototypes according to previous studies [19,53]. Some researchers have proved that most fine particles in the pore structure are rushed out under the seepage force action and the seepage channels gradually develop and become interconnected in the seepage process by permeability test [54,55]. It can be seen that the landslide moves or slides along these holes or fissures, which were developed or produced by seepage erosion.…”
Section: Seepage Erosionmentioning
confidence: 55%
“…This phenomenon can also be found in the prototypes according to previous studies [19,53]. Some researchers have proved that most fine particles in the pore structure are rushed out under the seepage force action and the seepage channels gradually develop and become interconnected in the seepage process by permeability test [54,55]. It can be seen that the landslide moves or slides along these holes or fissures, which were developed or produced by seepage erosion.…”
Section: Seepage Erosionmentioning
confidence: 55%
“…Compared with the dam crest overflow failure, the seepage failure is more difficult to find and detect and easy to cover up in the dam crest overflow failure. Some researches showed that piping and internal erosion caused by seepage were one of the main causes of landslide dam failure [23,24]. The peak discharge caused by seepage failure is more remarkable for higher dams than that caused by overtopping failure [25].…”
Section: Introductionmentioning
confidence: 99%
“…Model testing has become an essential method with which to study the stability of LDs, as in the works by Gregoretti et al (2010), Awal et al (2011), Chen et al (2015), Okeke and Wang (2016), Jiang et al (2018Jiang et al ( , 2019 and Dhungana and Wang (2019). In these studies, however, the grain size distribution of the LD material was not considered, and the model LD could only re ect part of a real LD with limitations.…”
Section: Introductionmentioning
confidence: 99%